2019
DOI: 10.22270/jddt.v9i4-s.3315
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation and Validation of Chlorthlidone and Azilsartan Medoximil in Bulk and Tablet Dosage Form by using RP-HPLC

Abstract: The first reversed phase high performance liquid chromatographic method for Stability Indicating of, Azilsartan and chlorthalidone has been developed and validated to be a simple, sensitive, rapid, specific, precise, and accurate method. Chromatographic separation was achieved on Zorbax XBD-C8, 250mm × 4.6mm,5µm.Buffer pH5.5 : Methanol  (60:40) as a mobile phase at flow rate of 1 ml/min. UV detection was operated at 234 nm and injection volum was 25 μl.. The proposed method showed good linearity, accuracy, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…The chemical structures of AZL and CIL are shown in Figure 1. Numerous RP-HPLC methods have been published in the literature for the estimation of AZL alone and with other drugs [12][13][14][15][16][17][18][19][20], CIL alone, and with other drugs [21][22][23][24][25] in their FDCs. Recently, some chromatographic methods such as RP-HPLC and ultra-performance liquid chromatography methods have been reported in the literature for simultaneous estimation of AZL and CIL using class 2 solvents (methanol and acetonitrile) as mobile phase and diluent [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of AZL and CIL are shown in Figure 1. Numerous RP-HPLC methods have been published in the literature for the estimation of AZL alone and with other drugs [12][13][14][15][16][17][18][19][20], CIL alone, and with other drugs [21][22][23][24][25] in their FDCs. Recently, some chromatographic methods such as RP-HPLC and ultra-performance liquid chromatography methods have been reported in the literature for simultaneous estimation of AZL and CIL using class 2 solvents (methanol and acetonitrile) as mobile phase and diluent [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…3 Azilsartan is crystalline powder in nature having off-white color and soluble in methanol and partially soluble in acetonitrile and insoluble in water. The literature review on the availability of analytical methods for Azilsartan revealed a UV spectroscopic method, 7 few ultra-performance liquid chromatographic method and LC-MS methods for the quantification of Azilsartan in bulk drug, plasma 8,9 and combination with other drugs 10,11 and stability-indicating high-performance thin layer chromatographic (HPTLC) method. 12 In the literature survey, many chromatographic analytical methods were developed having several drawbacks include high buffer concentration leads to column damage, time-consuming and tedious.…”
Section: Introductionmentioning
confidence: 99%